Introduction of Luwu Culture Through Adobe Flash Educational Game: Its Influence on Elementary School Students' Metacognition - Ahmiranti, Ahmiranti; Suryani, Lilis; Nursyamsi (Journal of Social and Scientific Education, 2024)
This study aims to evaluate the effectiveness of introducing Luwu culture through educational word puzzle games on students' metacognitive abilities. The research method used is the experimental design of one group pretest-posttest with a sampling technique using saturated sampling, resulting in a sample size of 14 students. Data collection is done through tests, observations, and questionnaires, with data analysis performed descriptively. The results show that the use of educational game media is effective for students, indicated by a significant increase in their usage through the educational word puzzle game media with an n-gain value of 0.48, active participation of students at 84%, and positive responses from students regarding the use of educational word puzzle games at 80%.